SOME REPRODUCTION CHARACTERISTICS OF LONGTAIL TUNA CAUGHT IN THE SEA WATERS OF KHANH HOA PROVINCE - Phuoc, Tran Van (Vietnam Journal of Marine Science and Technology, 2009)
This study presents some reproduction characteristics of Longtail tuna caught in the sea waters of Klzanh Hoa province. The tota l number of gonads collected during the research period was 79 in which gonads of stages from I, II, III, IV were 44.30%, 40.51%; 6.33% and 8.86% respectively. Gonads maturity stage IV (developing stage) of the fish was defined from September to December. The fork length of first maturity of Longtail tuna was 44 cm. The ratio of male andfemale was 1. 2:1.0